Trade Globalization, Remittance Inflows, and Environment Nexus in the Middle East and North Africa: Cross-Sectional Dependence Analysis - Mahmood, Haider; Saqib, Najia (International Journal of Energy Economics and Policy, 2025)
Trade globalization and remittance inflows can support economic growth. However, these indicators might have environmental problems due to scale effects in any economy and could be a hurdle in achieving target numbers 8 and 13 of the sustainable development goals (SDGs). Thus, the effects of exports, imports, remittance inflows, and economic growth on CO2 emissions are tested in 16 MENA economies by using the period 2001-2022 and by using cross-sectional dependence (CSD) econometric techniques. The results confirm the Environmental Kuznets curve (EKC) hypothesis with a threshold point of 13,181 US dollars. 6 out of 16 investigated economies are found in the second phase of the EKC and economic growth could have a pleasant effect in these economies. However, the effects of exports, imports, and remittance inflows on CO2 emissions are found positive in the long run. Therefore, exports, imports, and remittance inflows have environmental problems in this region. Thus, the research proposes to impose taxes on exports, imports, and remittance inflows to mitigate their environmental effects.